Review: IV International Experimental Archaeology Conference, Burgos 2014 - Francisco Javier San Martin Gonzalez (EXARC Journal)
For four days in Burgos (Spain) 235 people from 15 countries gathered for the fourth, and most international thus far, Congress of Experimental Archaeology, organized by EXARC, Experimenta, the Museum of Human Evolution, and the Universidad Autónoma de Madrid.